Analisis Tingkat Kepuasan Konsumen Melon di Hortimart Agro Center Kabupaten Semarang - Thahira, Zahwa Nauria; Prastiwi, Wahyu Dyah; Mukson, Mukson (Universitas Galuh, 2024)
Consumer satisfaction is a condition where consumers expect products or services that are in accordance with their wishes. The study aimed to analyze the level of Melon’s consumers’ satisfaction at Hortimart Agro Center based on variables of product quality, price, service quality and promotion. The research was expected to bring benefit in determining the policies taken by the Hortimart Agro Center to increase Melon’s customers’ satisfaction. The research was conducted from February to March 2023. The research location was at Hortimart Agro Center. The research method used in the study was a survey. Respondents were determined by accidental sampling method with a sample size of 100 respondents. Data analysed were using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) analysis to analyze the level of Melon’s consumers’ satisfaction at Hortimart Agro Center based on the factors that affect consumer satisfaction namely product quality, price, service quality and promotion. The results showed that there are in Quadrant I (two attributes namely design and promotional publicity), Quadrant II (ten attributes namely quality, taste, durability, benefits, price in accordance with quality, as well as reliable and responsive Hortimart employee services), Quadrant III (four attributes namely affordable prices than prices elsewhere and Hortimart promotions through advertising media and brochures), Quadrant IV (no attributes). Melon’s consumers’ satisfaction value at Hortimart Agro Center reached 83.05% which is in the very satisfied category.